miR-223: a key regulator of pulmonary inflammation - Shi, Mingyu; Lu, Qianying; Zhao, Yanmei; Ding, Ziling; Yu, Sifan; Li, Junfeng; Ji, Mengjun; Fan, Haojun; Hou, Shike (Frontiers in Medicine, 2023)
Small noncoding RNAs known as microRNAs (miRNAs) are vital for the regulation of diverse biological processes. miR-223, a well-conserved anti-inflammatory miRNA expressed in cells of the myeloid lineage, has been implicated in the regulation of monocyte-macrophage differentiation, proinflammatory responses, and the recruitment of neutrophils. The order of the coordinated nouns has been changed while keeping the meaning of the sentence the same. The structure of the sentence is also different from the original sentence. The biological functions of this gene are regulated by its expression levels in cells or tissues. In this review, we first outline the regulatory role of miR-223 in granulocytes, macrophages, endothelial cells, epithelial cells and dendritic cells (DCs). Then, using pulmonary inflammation markers, we summarize the possible role of miR-223 in chronic obstructive pulmonary disease (COPD), acute lung injury (ALI), coronavirus disease 2019 (COVID-19) and other pulmonary inflammatory diseases to better understand the molecular regulatory networks in pulmonary inflammatory diseases.